An analysis of e-banking as a cost reduction method at Central Africa Building Society (CABS). - Muguzuri, Happymore (Midlands State University, 2017)
The main thrust of the study was to carry an analysis of e-banking as a costs reduction measure at CABS. The focus was on the analysis of the effectiveness of the e-banking model at CABS. A research was prompted as many authors castigated that e-banking present banks with a perfect opportunity to reduce costs and maximize profits but after having introduced e-banking at CABS costs did not reduce thereby creating a basis for researching into the reasons why. Empirical evidence was gathered from books and newspapers on the main objective of ebanking, advantages and challenges in the implementation of e-banking model, challenges linked with the adoption and factors that are fundamental for the success of e-banking. The writer made use of the descriptive research design hence the findings were gathered through the use of questionnaires and interviews. The results showed that the main objective of e-banking was to reduce costs but overly costs kept on rising due to several factors. It was noted that though there were rising costs there were some advantages enjoyed through the use of the e-banking model. Recommendations that were suggested included continuous programs of training and retaining of key personnel, formulation and enforcing of security policies, and adoption of e-banking in its entirety.